(untitled) (Transport systems and technologies, 2022)
The article deals with the models of dump cars, which form the major part of the mainline railway car fleet of 1520 mm. The technical characteristics of the most common mainline dump cars models are given. The design features of the dump car model 31-638, designed for transportation and mechanized unloading of bulk and lump cargo, are presented. Modern models of dump cars of domestic and foreign production for the main railway transport of 1520 mm track, which were constricted and put into serial production in recent years, are presented. The results of comparative analysis of technical characteristics of dump cars of the last generation to modern models of dump cars showed that one of the main advantages of the latter is reduction of container weight, increase of load capacity and body volume, improving of strength and reliability of separate units and systems. The problem units and systems of the existing models of main-line dump cars are determined based on the results of their operation, which need further strengthening. The focus areas of improving the design of modern models of dump cars for the 1520 mm main railway vehicles are defined. The technical requirements for the next generation dump cars, which are planned to be constructed and put into serial production in the coming years for operation on the mainline railway tracks, are proposed. The technical requirements are formed taking into account the research results of modern mainline dump cars design, review of technical and design documentation for these railway vehicles, as well as analysis of requirements and wishes of customers. The necessity of carrying out relevant research and engineering works on the development of new generation dump cars for the main railway transport is substantiated. The content of the article will contribute to the construction of new models of dump cars for the main railway transport and significant upgrading of existing models, as well as increase the efficiency of their operation.